RNA binding protein ALYREF regulates ferroptosis to facilitate LUAD growth and metastasis via promoting SLC7A11 mRNA stability - Yanni Chen; Ting Zhao; Hao Chen; Jun Chen; Weili Han (Scientific Reports)
Abstract Ferroptosis is of great significance in carcinogenesis as it interconnects with a multiplicity of biological processes. Meanwhile, its function and regulatory role in lung cancer remains ambiguous. In this study, we discovered by WB and IHC that ALYREF has a higher expression in lung adenocarcinoma (LUAD) tissues compared with normal ones. By the direct observation of mitochondria with electron microscopy, we also identified that the knockdown of ALYREF limits the proliferation of LUAD in vitro as well as in vivo and prompts LUAD cells to go through ferroptosis. Mechanistically, our RNA-immunoprecipitation experiment combined with qRT-PCR analysis confirmed that ALYREF could interact with SLC7A11. ALYREF mainly binds to the 3’UTR region of SLC7A11 mRNA, increasing the mRNA stability of SLC7A11 and reducing intracellular Reactive Oxygen Species (ROS) and Methylene diphenyl diamine (MDA) thereby inhibiting ferroptosis and eventually promoting the proliferation and metastasis of LUAD cells. Importantly, our study reveals for the first time that ALYREF can regulate LUAD by inhibiting ferroptosis. Based on the evidences mentioned above, we have good reason to believe that the role of ALYREF as a new oncological factor could be proved and, acting along the ALYREF-SLC7A11-ferroptosis axis, utilized as a promising therapeutic target for LUAD.